BAHAN ALAMI SEBAGAI PEWARNA BAGI RUBBER BASIS AIR PADA MEDIA KERTAS DAN KAIN - M. Danang Syamsi; Donna Carrollina (AKSA: Jurnal Desain Komunikasi Visual, 2021)
Screen printing is one of the printing techniques in graphic design. In general, the materials used in the screen-printing process are screen and rubber. Where from these two materials in the end the design in the form of a film can be transformed into the media to be screened. The popular rubber used today is rubber mixed with chemical dyes. Where these chemicals are not environmentally friendly, it is necessary to explore the use of natural-based dyes from plants as dyes for screen-printing rubber. This research is an experimental study conducted to determine the potential use of natural materials as dyes for water-based rubber screen-printing on printing media such as fabric. The research method used is experiment method. The result of the experiment is several plants can be extracted as a dye, but has a light color that not expectected and also can implanted on canvas fabric but with color didn’t match as expected.